High-order finite element model of bridge rubber bearings for the prediction of buckling and shear failure. (1st August 2021) - Saidou, Adamou; Gauron, Olivier; Busson, Arnaud; Paultre, Patrick
Highlights: A 3D FEM for layered elastomeric bridge bearings and isolators is investigated. The model is able to predict accurately the lateral stability limit and the shear failure. The model is suitable for numerical and parametric studies to develop design guideline. Of the several rubber material models compared, the Ogden model is found the most suitable. The FEM using the Ogden formulation is validated on experimental shear-compression tests results. Abstract: Performance-based design is becoming the main design method for highway bridge seismic design. This design method requires a good knowledge of the damage mechanisms of each component of the bridge. Rubber bearings and isolators represent a key component of the earthquake-resistance system of bridges that can experience large lateral displacements while supporting high axial loads. Rubber bearings and isolators can thus experience lateral instabilities under seismic loading, resulting in ultimate limit states by buckling or by shear failure depending on the geometry of the bearing. This paper investigates the development of a general numerical 3D finite element model for layered elastomeric bridge bearings and isolators that is able to accurately predict both limit states under shear-compression loadings at very large deformations. Such a model is aimed at subsequent utilization in large numerical and parametrical studies to develop practical and accurate design guidelines for the limit states of bridge rubber isolators. In this study, the accuracy of several rubber finite element formula tions has been studied, including the often used low-order and easy-to-calibrate Mooney-Rivlin and Neo-Hookean models and the two high-order Arruda-Boyce and 6-parameter Ogden models. For the latter model, a calibration procedure is proposed based on three simple standard characterization tests of the material that circumvents the much higher difficulty of calibration of the Ogden model compared to the others. The calibration results for the four considered models show that the 6-parameter Ogden model surpasses the ability of the three other models to accurately represent the material behavior in the different deformation modes experienced by rubber bearings under shear compression at large deformations. The four models are then compared for their ability to predict the force–displacement curves of some experimentally tested isolators. The Ogden model showed again higher accuracy compared to the other models that are mostly used in literature. The finite element model based on the Ogden formulation is finally completely validated by using extensive experimental results obtained from tests performed on real-scale rubber bearings and isolators of various shape factors and slenderness values. Finally, for nonslender bearings that experience shear failure at large deformation, a numerical material failure criterion is proposed and validated by comparing the critical displacement predictions of the model to the available experimental results.